Analisis Penerapan E-Faktur Terhadap Kepatuhan Wajib Pajak (Studi Kasus Pada PT BGR Logistik Indonesia Cabang Semarang) - Ardiyani, Nia; Raditya Tantra, Arda (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2024)
Tax Services in the Java and Bali regions, especially in Central Java, there is an obligation to use an electronic tax invoice (e-Invoice) to improve the efficiency of tax administration. The purpose of making this e-Invoice is a step to avoid forms of deviation, this is an evolution of the efforts of the Directorate General of Taxes to improve the administration of Value Added Tax (VAT). The Semarang branch of the logistics company, namely PT BGR Logistik Indonesia, offering digital-based logistics service solutions with a wide network, has also implemented an e-Invoice system to make it easier to make consumer tax invoices that have made warehouse rental transactions, logistics services, and Supply Chain Management Profider. This research method uses a qualitative method, and the data source obtained from the subject of the origin of this research data uses Primary Data, data collection techniques involve observation, interviewing, and documentation while the process of qualitative data analysis begins with data collection, data reduction, data presentation, and conclusion. With the E-Invoice system, it can help and facilitate the creation of Value Added Tax (VAT) and also minimise errors that occur. If the system runs well, it will help the productivity of daily activities in the collection of receivables, especially knowing the collected taxes.